O papel da Universidade Estadual do Oeste do Paraná no ecossistema de inovação da região oeste do Paraná - Corrêa, Cathia Petranski (2021)
Innovation has taken part of an essential part for growth and socioeconomic development. In addition, it is able to provide the creation of new business models, and to fulfill the needs of different kinds of consumers. It encourages scientific and technological knowledge, it provides different effective ways of competition in business fields and the generation of entrepreneurial cooperation environments, called Innovation Ecosystem, which stimulate the creation of innovative projects and the exchange of productive experiences, synergistically among the actors involved. The government, universities, industries, support institutions, entrepreneurs, financial system, customers and society are in this environment. In this context, the university assumes the role of contributing to economic, social and cultural development according to the research production, which aims at generating results for organizations, providing new applicable knowledge and training new entrepreneurs. However, its role goes beyond teaching and researching, as it takes on a third mission when it proposes to develop its region based on technological innovations. Thus, the university stands out as one of the main actors within its ecosystem. Therefore, this study aimed at understanding the role played by the Western Paraná State University in the Innovation Ecosystem of the Western Paraná region in order to solve problems and meet the social needs of this region. The study is characterized as exploratory and descriptive. The procedures are bibliographic and documentary and the approach is qualitative. In order to structure the theoretical part of this research, a systematic literature review was carried out by searching on national and international bibliographies. For the survey of primary data, a semi-structured script with open questions was applied to the actors that made part of the ecosystem of western Paraná. As results, it is possible to reach the proposed objective of the present study, which has shown several entrepreneurial actions carried out by the university. This study also induced some challenges and conditioning factors as a result, which impacted on the University / Company cooperation. Finally, practical actions were suggested to improve UNIOESTE, and contribute to the regional development in a sustainable way within the Innovation Ecosystem of the western Paraná region.